De novo PHIP-predicted deleterious variants are associated with developmental delay, intellectual disability, obesity, and dysmorphic features - Webster, Emily (Cold Spring Harb Mol Case Stud, 2016)
Using whole-exome sequencing, we have identified novel de novo heterozygous pleckstrin homology domain-interacting protein (PHIP) variants that are predicted to be deleterious, including a frameshift deletion, in two unrelated patients with common clinical features of developmental delay, intellectual disability, anxiety, hypotonia, poor balance, obesity, and dysmorphic features. A nonsense mutation in PHIP has previously been associated with similar clinical features. Patients with microdeletions of 6q14.1, including PHIP, have a similar phenotype of developmental delay, intellectual disability, hypotonia, and obesity, suggesting that the phenotype of our patients is a result of loss-of-function mutations. PHIP produces multiple protein products, such as PHIP1 (also known as DCAF14), PHIP, and NDRP. PHIP1 is one of the multiple substrate receptors of the proteolytic CUL4-DDB1 ubiquitin ligase complex. CUL4B deficiency has been associated with intellectual disability, central obesity, muscle wasting, and dysmorphic features. The overlapping phenotype associated with CUL4B deficiency suggests that PHIP mutations cause disease through disruption of the ubiquitin ligase pathway.